Effect of oxygen and biofilms on crevice corrosion of UNS S31803 and UNS N08825 in natural seawater - Machuca, Laura; Bailey, Stuart; Gubner, Rolf; Watkin, Elizabeth; Ginige, M.; Kaksonen, A.; Heidersbach, K. (Pergamon, 2013)
The effect of oxygen and biofilms on crevice corrosion of UNS S31803 and UNS N08825 in seawater was studied. Passivity breakdown occurred through crevice corrosion in UNS N08825 and through transpassive dissolution in UNS S31803 although both alloys displayed crevice corrosion under potentiodynamic conditions. The most severe crevice corrosion occurred in the absence of oxygen and the presence of a biofilm. Microbial adhesion as investigated by fluorescence microscopy occurred mainly outside the crevice and DNA sequencing revealed a shift in biofilm composition as a function of substratum surface and oxygen pressure.